Early tumour response as a survival predictor in previously- treated patients receiving triplet hepatic artery infusion and intravenous cetuximab for unresectable liver metastases from wild-type KRAS colorectal cancer. - Bouchahda, M (2016)
BACKGROUND: Surgery for colorectal liver metastases results in an overall survival of about 40% at 5 years. Progression-free survival is increased with the addition of oxaliplatin and fluorouracil chemotherapy. The addition of cetuximab to these chemotherapy regimens results in an overall survival advantage in patients with advanced disease who have the KRAS exon 2 wild-type tumour genotype. We aimed to assess the benefit of addition of cetuximab to standard chemotherapy in patients with resectable colorectal liver metastasis. METHODS: Patients with KRAS exon 2 wild-type resectable or suboptimally resectable colorectal liver metastases were randomised in a 1:1 ratio to receive chemotherapy with or without cetuximab before and after liver resection. Randomisation was done using minimisation with factors of surgical centre, poor prognostic tumour (one or more of: ≥ 4 metastases, N2 disease, or poor differentiation of primary tumour), and previous adjuvant treatment with oxaliplatin. Chemotherapy consisted of oxaliplatin 85 mg/m(2) intravenously over 2 h and fluorouracil bolus 400 mg/m(2) intravenously over 5 min, followed by a 46 h infusion of fluorouracil 2400 mg/m(2) repeated every 2 weeks (regimen one) or oxaliplatin 130 mg/m(2) intravenously over 2 h and oral capecitabine 1000 mg/m(2) twice daily on days 1-14 repeated every 3 weeks (regimen two). Patients who had received adjuvant oxaliplatin could receive irinotecan 180 mg/m(2) intravenously over 30 min with fluorouracil instead of oxaliplatin (regimen three). Cetuximab was given as an intravenous dose of 500 mg/m(2) every 2 weeks with regimen one and three or a loading dose of 400 mg/m(2) followed by a weekly infusion of 250 mg/m(2) with regimen two. The primary endpoint was progression-free survival. This is an interim analysis, up to Nov 1, 2012, when the trial was closed, having met protocol-defined futility criteria. This trial is registered, ISRCTN22944367. FINDINGS: 128 KRAS exon 2 wild-type patients were randomised to chemotherapy alone and 129 to chemotherapy with cetuximab between Feb 26, 2007, and Nov 1, 2012. 117 patients in the chemotherapy alone group and 119 in the chemotherapy plus cetuximab group were included in the primary analysis. The median follow-up was 21.1 months (95% CI 12.6-33.8) in the chemotherapy alone group and 19.8 months (12.2-28.7) in the chemotherapy plus cetuximab group. With an overall median follow-up of 20.7 months (95% CI 17.9-25.6) and 123 (58%) of 212 required events observed, progression-free survival was significantly shorter in the chemotherapy plus cetuximab group than in the chemotherapy alone group (14.1 months [95% CI 11.8-15.9] vs 20.5 months [95% CI 16.8-26.7], hazard ratio 1.48, 95% CI 1.04-2.12, p=0.030). The most common grade 3 or 4 adverse events were low neutrophil count (15 [11%] preoperatively in the chemotherapy alone group vs six [4%] in the chemotherapy plus cetuximab group; four [4%] vs eight [8%] postoperatively), embolic events (six [4%] vs eight [6%] preoperatively; two [2%] vs three [3%] postoperatively), peripheral neuropathy (six [4%] vs one [1%] preoperatively; two [2%] vs four [4%] postoperatively), nausea or vomiting (four [3%] vs six [4%] preoperatively; four [4%] vs two [2%] postoperatively), and skin rash (two [1%] vs 21 [15%] preoperatively; 0 vs eight [8%] postoperatively). There were three deaths in the chemotherapy plus cetuximab group (one interstitial lung disease and pulmonary embolism, one bronchopneumonia, and one pulmonary embolism) and one in the chemotherapy alone group (heart failure) that might have been treatment related. INTERPRETATION: Addition of cetuximab to chemotherapy and surgery for operable colorectal liver metastases in KRAS exon 2 wild-type patients results in shorter progression-free survival. Translational investigations to explore the molecular basis for this unexpected interaction are needed but at present the use of cetuximab in this setting cannot be recommended.